Recurrent Pregnancy Loss (Springer Singapore, 2018)
This book covers the entire topic extensively, from demographics to recent and future management options. A special section on the role of controversial strategies has also been included. Lastly, the book features dedicated chapters on evidence-based approaches, which include step-by-step algorithms for the reader's convenience.